Beyond the Balance Sheet: Uncovering Intellectual Capital in Acquisitions A study of how to strategically manage intellectual capital in an M&A process - Danielsson, Alexander; Torstensson, Felicia (My University, 2023)
In 2021, the global M&As conducted exceeded 62 000. The recent M&A activity has been fueled by intense demand for technology, and for digital and data-driven assets. However, studies show that the failure rate of M&As is between 70-90%. One of the reasons behind the high failure rate has been linked to a lack of identification of intellectual capital in the due diligence phase and to a lacking focus on how to retain it. Intellectual capital is an intangible resource that, in comparison to tangible, it is more difficult both to identify and evaluate. However, when ignoring intellectual capital in the acquisition, which often is the source of the competitive advantage, the firm might not be able to use the assets in an effective way after the acquisition is completed. The role of intangible assets, particularly human- and relational capital, in the success or failure of M&A transactions has received little attention in academic literature. Through a multiple case study, this thesis investigates how intellectual capital management can impact the outcome of an acquisition of intangible-intensive firms. More specifically, through intellectual capital in the form of innovation-, human-, and relational capital. The study covers the strategic objectives behind acquiring intellectual capital, its associated risks, ways of mitigating the risks, and how to better understand what is being acquired. The findings in this study show that in order to keep the value of the acquired assets, the acquiring firm needs to avoid the risk of losing the individuals that possess relevant technology-related know-how, R&D capabilities, and tacit knowledge regarding how to manage the relational capital in the form of customers and suppliers. Furthermore, the acquirer of the intellectual capital is subjected to many risks in relation to controlling the intellectual capital, e.g., through intellectual property rights and contracts. In order to mitigate these risks, and several others, the findings in this study show that a proactive approach can positively impact the outcome of an acquisition of an intangible-intensive firm. The proactive approach consists of identifying, evaluating, and managing the intellectual capital earlier in the M&A process. The outlined process consists of four phases, where (1) Utilization, refers to connecting the acquisition strategy with the intellectual capital activities throughout the M&A process. (2) Identification, and (3) Evaluation, refers to an early stage (i) identification and evaluation of the intellectual capital, (ii) its risks and (iii) its control positions related to the strategic objective. (4) Manage, refers to either conducting measures to ensure this before the acquisition is closed or to create a detailed plan of what measures need to be taken after the closing.
Keywords: Acquisitions; Intangible assets; Intellectual capital; Intellectual capital management; Intellectual assets; Innovation Capital; Human Capital; Relational Capital; Technology, Knowledge; Relationships; Utilization; Identification; Evaluation; Managing